Analyzing the Effect of Transformational Leadership and Self-Efficacy on Employee Performance through Employee Innovativeness among Employees of PERUMDA Tirtanadi Sunggal Medan - Sabila, Jihan; Absah, Yeni; Harahap, R. Hamdani (Indonesian Journal of Advanced Research, 2025)
This study analyzes how transformational leadership and self-efficacy influence employee performance at Perumda Tirtanadi KC Sunggal Medan, with employee innovativeness as a mediating variable. Using a quantitative approach with PLS-SEM on census data from 50 employees, the research evaluates both direct and indirect relationships. The results show that transformational leadership does not significantly affect employee innovativeness or performance, likely due to a highly structured, SOP-driven public sector environment. In contrast, self-efficacy has a positive and significant impact on both innovativeness and performance. Employee innovativeness also significantly improves performance and mediates the effect of self-efficacy on performance, but not the effect of transformational leadership. The study concludes that psychological factors—especially self-efficacy and innovative behavior—are more influential than leadership style in enhancing performance within regulated public utility organizations.